The effects of remittances on poverty alleviation in developing countries - Ow, Celine Shu Han (2016)
Inflows of international remittances have been increasing over the past decades. However, the poverty-reducing effect of remittances at a cross-country level has not been adequately studied. This paper examines the impact of remittances on poverty alleviation through the interaction of remittances with education, trade and financial development and how their effects vary among the extreme and moderate poverty groups. Using a panel dataset from 113 developing countries, the paper finds that while remittances have a complementary effect with trade openness, remittances have no significant effect with financial development in poverty reduction. Moreover, remittances only complement education in poverty alleviation for the moderate poverty group. Most importantly, consistent findings indicate that remittances help alleviate poverty in the moderate poverty group, while the same effect is insignificant in the extreme poverty group. The results are robust to the use of varying instruments and endogeneity issues are also addressed.